Experiencing the landscape in antiquity - Cristilli, Armando 1972-; Gonfloni, Alessia (BAR Publishing, 2020)
This book contains the papers presented at the 3rd International Conference of Classical Antiquities, entitled 'Experiencing the Landscape in Antiquity 3', held in Rome on 29th to 31st May 2023 at the Department of Literary, Philosophical and Art History Studies of the University of Rome 'Tor Vergata'. The ancient landscape is an important theme, well-suited to interdisciplinary research which is a feature of the research projects currently ongoing at 'Tor Vergata'. In line with this tradition, this conference aimed to stimulate dialogue between different disciplines, from archaeology to ancient history, from epigraphy to literature and numismatics on the ancient Mediterranean between the 7th century BC and the 7th century AD. In this way, innovative research, original methodologies and comparative studies are presented
Conference proceedings
Keywords: Landscapes / Mediterranean Region / Congresses; Mediterranean Region / History / To 1500 / Congresses; Konferenzschrift